Modular robot gripper light weight concept - Lakshmanan, Subramanian; Mohan, Suvyaktha (My University, 2023)
Volvo Cars Corporation’s (VCC) Technology development department is interested in investigating the feasibility study of a new gripper solution proposed by a supplier (ThyssenKrupp). The existing gripper profiles in VCC are made from Aluminum and welded Steel. VCC is facing a critical issue where the profiles get cracked or snapped under a crash. This disturbs the lead time within the production line and involves a lot of cost in replacing the damaged system. Also, the weight of the grippers is increasing to handle new operations and requires adding new gripping components and subcomponents. This is in turn affecting the Motor load and causing performance issues with robots. To solve these issues, ThyssenKrupp produced a new Gripper Profile concept made of Steel for implementing with all the robots. Considering the proposal and analyzing the challenges faced in existing techniques at VCC, this thesis aims to investigate the advantages and disadvantages of the new concept proposed by ThyssenKrupp and formulate conclusions about the proposed solution with respect to various aspects like Material, Mechanical properties, Weight, Energy consumption, Cost and Sustainability. In this study, three grippers have been selected as sample data to study the system. The investigation will plot the effects on these selected grippers and differences between Aluminum gripper profile and steel gripper profile.
Keywords: Modular grippers, pre-galvanized steel, weight, energy consumption.